Towards a social investment welfare state? : Ideas, policies and challenges / edited by Nathalie Morel, Bruno Palier and Joakim Palme. - Morel, Nathalie; Palier, Bruno; Palme, Joakim (Policy, 2012)
This book maps out the contours of the European 'social investment' strategy, both at the ideational level and in terms of the policies implemented throughout Europe. It will appeal to both social policy scholars and policy experts.